An integrated shortfall measure for Basel III - Ingo Torchiani; Thomas Heidorn; Christian Schmaltz (Deutsche Bundesbank, 2017)
We propose a new method for measuring how far away banks are from complying with a multi-ratio regulatory framework. We suggest measuring the efforts a bank has to make to reach compliance as an additional portfolio which is derived from a microeconomic banking model. This compliance portfolio provides an integrated measure of the shortfalls resulting from a new regulatory framework. Our method complements the descriptive reporting of individual shortfalls per ratio when monitoring banks' progress toward compliance with a new regulatory framework. We apply our concept to a sample of 46 German banks in order to quantify the effects of the interdependencies of the Basel III capital and liquidity requirements. Comparing our portfolio approach to the shortfalls reported in the Basel III monitoring, we find that the reported shortfalls tend to underestimate the required capital and to overestimate of the required stable funding. However, compared to the overall level of the reported shortfalls, the effects resulting from the interdepen- dencies of the Basel III ratios are found to be rather small.
Keywords: G21; C61; 330; Basel III; linear programming; impact studies; integrated shortfall